Uncovering the Psychological Impact of Domestic Violence: A Case Study on Housewives in Village Asei Besar East Sentani District Jayapura Regency - Hasmi, Hasmi; Makaba, Sarce (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: Forty percent of women in Papua experience domestic violence, and one of the causes is alcohol consumption. Violence against housewives impacts maternal psychic. This research aims to identify the types of domestic violence and their psychic impact and identify the dominant violence affecting them. Method: Data on domestic violence were collected using the Rasyid Questionnaire and Psychological Variables using a questionnaire developed by the World Health Organization, namely WHO QoL-BREF. Univariate, bivariate, and multivariate analysis was used to study the forms of violence that affect the psychic of housewives. Result: The highest form of violence having a psychological impact was sexual; domestic violence was 86 (100%). The highest psychological impact of housewives is not feeling satisfied and not proud of themselves 103 (78%). The most sequentially significant types of domestic violence are sexual violence P value; 0.000, Having an affair (p-value; 0.001), Mild physical violence (p-value; 0.004); psychological violence: abuse, humiliation (P value; 0.013, harassment, insulting (P value; 0.017), drunkenness and spanking (p-value;0.028), violence kicking, hitting, attempted murder of family members at home (0.038), irritability (p-value; 0.04). The most dominant influence on the mother's psychological is having an affair p-value of 0.015 and OR 14.2 (1.6-122.4). Conclusion: The most common form of violence is hitting, trapping, and pushing, and the dominant form of violence affecting the mother's psyche is that the husband has an affair. It is necessary to monitor and identify domestic violence, especially in pregnant women, which is integrated with Antenatal Care and services at the Community Health Center.